2013
DOI: 10.7567/jjap.52.08jn02
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement-Mode LaLuO3–AlGaN/GaN Metal–Insulator–Semiconductor High-Electron-Mobility Transistors Using Fluorine Plasma Ion Implantation

Abstract: Carbon monosulfide molecular ion (CS + ), which plays an important role in various research fields, has long been attracting much interest. Because of the unstable and transient nature of CS + , its electronic states have not been well investigated. In this paper, the electronic states of CS + are studied by employing the internally contracted multireference configuration interaction method, and taking into account relativistic effects (scalar plus spin-orbit coupling). The spinorbit coupling effects are consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…With L GD = 10 µm, the catastrophic breakdown of the E‐mode HEMT occurs at a drain voltage of 450 V even measured in air (see Fig. c), which is, to the best of our knowledge, the highest value of the E‐mode HEMT fabricated using plasma oxidation technology and comparable to results obtained by other technologies with similar L GD . An enhanced breakdown performance can be expected when the large OFF‐state leakage current possibly originating from a stronger polarization electric field in Al‐rich barrier layer is further suppressed .…”
Section: Resultssupporting
confidence: 68%
“…With L GD = 10 µm, the catastrophic breakdown of the E‐mode HEMT occurs at a drain voltage of 450 V even measured in air (see Fig. c), which is, to the best of our knowledge, the highest value of the E‐mode HEMT fabricated using plasma oxidation technology and comparable to results obtained by other technologies with similar L GD . An enhanced breakdown performance can be expected when the large OFF‐state leakage current possibly originating from a stronger polarization electric field in Al‐rich barrier layer is further suppressed .…”
Section: Resultssupporting
confidence: 68%
“…Terbium IV oxide films have huge application as an insulator in microelectronics, gas detectors, and luminophores due to unique properties such as radiation resistance and very small leakage current density besides variable electrical conductivity in different gaseous fluids [4,5]. It is found that various oxidation states cause changes in the stoichiometry of terbium IV oxide that predetermines variations in its optical properties, thus making it useful for the aforementioned applications as well as in Fresnel lenses, pigments, antireflection layers, and photoelastic films [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…A normally-off AlGaN/GaN HEMT device with a positive gate threshold voltage (V TH > 0) is desirable in power applications due to the benefits of system controllability. To make such devices, three techniques are available: the p-GaN (or p-AlGaN) cap layer [1,2], AlGaN barrier recess [3,4], and the fluorine ion (F − ) treatment [5][6][7][8][9]. The p-GaN cap layer is Mg-doped and located underneath the gate contact to form a p-n junction between the p-GaN and i-AlGaN layers and to deplete the two-dimensional electron gas (2DEG).…”
Section: Introductionmentioning
confidence: 99%
“…Thirdly, there is the fluorine treatment technique by incorporating negative charges in the gate dielectrics to deplete the 2DEG. The amount of negative charge incorporated by the fluorine treatment is the key to determine the level of V TH [5][6][7][8][9]. For the unannealed multiple F − treatments on the ALD-Al 2 O 3 gate dielectric combined with a partial AlGaN recess reported in [11], a high amount of F − incorporation at the gate stack was possible, which resulted in a high threshold voltage of +6.5 V, with satisfactory maximum drain current (I DMAX ) of 340 mA mm −1 and off-state breakdown voltage of 1130 V. However, a large swing in the gate threshold voltage is found when devices operate at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%